The treatment of drinking problems a guide for the helping professions - Marshall, E. Jane; Humphreys, Keith; Ball, David M. (Cambridge medicine, 2010)
The Treatment of Drinking Problems has become the definitive text in the field of alcohol problems. It addresses the frontline realities of clinical practice in an informed and empathetic way, whilst grounding this approach in critical scientific review. Now in its fifth edition, the text has been thoroughly revised and updated with new sections covering interventions for hazardous and harmful drinking, dependent drinking, and the different settings in which alcohol problems are encountered. Clinical vignettes are used throughout the text to bring the discussion to life and to address the frontline realities of clinical practice. This is a highly readable and practical guide for anyone, generalist or specialist, treating or caring for someone with an alcohol problem